2008
DOI: 10.1111/j.1600-0846.2008.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel method to measure the elastic properties of skin including subcutaneous tissue: New age‐related parameters and scope of application

Abstract: This apparatus differs from other conventional instruments in that it measures the elastic properties of skin including subcutaneous tissue without contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…9 Nevertheless, elastography is said to have considerable clinical potential in the assessment of lower extremity vascular disease, pressure ulcers, lymphedema, and in the understanding of age-related changes in the skin. [9][10][11] It has been thought to have implications in the noninvasive characterization of skin tumors as well. 11 A recent presentation reviewing data from an elastographic assessment of benign and malignant neoplasms suggested that malignant lesions had significantly lower elasticity than benign lesions.…”
Section: Bccmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Nevertheless, elastography is said to have considerable clinical potential in the assessment of lower extremity vascular disease, pressure ulcers, lymphedema, and in the understanding of age-related changes in the skin. [9][10][11] It has been thought to have implications in the noninvasive characterization of skin tumors as well. 11 A recent presentation reviewing data from an elastographic assessment of benign and malignant neoplasms suggested that malignant lesions had significantly lower elasticity than benign lesions.…”
Section: Bccmentioning
confidence: 99%
“…[9][10][11] It has been thought to have implications in the noninvasive characterization of skin tumors as well. 11 A recent presentation reviewing data from an elastographic assessment of benign and malignant neoplasms suggested that malignant lesions had significantly lower elasticity than benign lesions. 12 …”
Section: Bccmentioning
confidence: 99%
“…In our previous study (6), we measured the elastic properties of the skin without actually contacting the skin. In addition, we have investigated the elasticity and viscosity of skin in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated age‐related changes in displacement of the skin in order to demonstrate the practical use of this apparatus to measure the elastic properties of the skin or other living tissues. Moreover, we reported that displacement profiles differ markedly between subjects, ages and body sites (6).…”
Section: Vertical Force Techniques (Fig 1)mentioning
confidence: 99%
See 1 more Smart Citation